Dynein and kinesin share an overlapping microtubule-binding site - Mizuno, Naoko (Nature Publishing Group, 2004)
Dyneins and kinesins move in opposite directions on microtubules. The question of how the same-track microtubules are able to support movement in two directions remains unanswered due to the absence of details on dynein–microtubule interactions. To address this issue, we studied dynein–microtubule interactions using the tip of the microtubule-binding stalk, the dynein stalk head (DSH), which directly interacts with microtubules upon receiving conformational change from the ATPase domain. Biochemical and cryo-electron microscopic studies revealed that DSH bound to tubulin dimers with a periodicity of 80 Å, corresponding to the step size of dyneins. The DSH molecule was observed as a globular corn grain-like shape that bound the same region as kinesin. Biochemical crosslinking experiments and image analyses of the DSH–kinesin head–microtubule complex revealed competition between DSH and the kinesin head for microtubule binding. Our results demonstrate that dynein and kinesin share an overlapping microtubule-binding site, and imply that binding at this site has an essential role for these motor proteins.